Practical approach to problems of the parturient diabetic in developing countries. Issue 6094 (22nd October 1977) - Sutton, C
Abstract : Improved management of diabetic pregnancies at Lautoka Hospital, Fiji, in 1976 resulted in a neonatal survival rate of 100%. Management included attempts to control the maternal blood glucose concentrations with insulin and delaying delivery until there was enough surfactant in the liquor to ensure a viable infant. The techniques are simple to use and require only minimal technological facilities.